Patterns of sensory and hedonic responses for salty and umami tastes and their impact on food familiarity, consumption, and nutritional status: A gender-based analysis from a large population sample - Camilla Cattaneo; Sara Spinelli; Caterina Dinnella; Cristina Proserpio; Erminio Monteleone; Ella Pagliarini; Monica Laureati (Current Research in Food Science)
In recent years, research on taste perception has increasingly focused on its influence on food consumption, preferences, and long-term health. While bitter and sweet tastes have been well-studied, less is known about salty and umami tastes and their effects on dietary habits. This study aimed to address this gap by exploring sensory-hedonic patterns for ‘savory’ stimuli, encompassing both umami and salty tastes, in a representative sample of Italian adults, with a focus on gender-specific differences. Associations among sensory-hedonic patterns, nutritional status, personality, and psycho-attitudinal traits, as well as food habits, were considered.Participants (n = 2878) rated their liking and intensity of salty, umami, and overall flavor sensations for bean purée with varying salt levels and provided anthropometric and food consumption data. K-means clustering identified specific sensory-hedonic patterns: ‘Dislikers’ and ‘Moderate Likers’ in women, and ‘Dislikers’ and ‘Likers’ in men. In both genders, the increased concentration of NaCl in the model food translated in opposite hedonic reactions, which was less evident in men with ‘Likers’ showing a higher preference for the saltiest sample. An overweight condition also characterized this latter group. Both 'Likers' clusters (regardless of gender) showed higher familiarity/consumption of less healthy foods, including high-calorie items, junk foods, meat, and fats (all p < 0.05). Gender-related differences were observed, with women preferring seafood and desserts, while men savory snacks and soft drinks. These results underscore taste's influence on dietary habits and the need to account for gender differences in personalized dietary interventions.